Improving the flow of petroleum products in pipelines using natural additives and powders - Nithiya, Arumugam (2012)
Liquids transportation through pipelines is considered one of the most power consuming sectors in the industry due to the turbulent mode these liquids are transported within. Skin friction formed by turbulent flow in pipe becomes the main aspect for researchers to explore the field of fluid mechanics. Frictional drag formed in pipelines transporting liquid can be reduced spectacularly by adding minute amounts of drag reducing agents. Drag reduction (DR) is a phenomenon where eddies changes its structure to interact with added material in transporting system for pumping power saving. During the past few decades, artificial additives were used to solve the problem. Most of these additives are not environmentally friendly with high level of toxicity. Therefore, in this present work two novel and environmentally friendly drag reducing agents were introduced. This thesis outlines the performance of natural additives and powders as drag reducing agent in transporting water and diesel via pipelines. The natural additives extracted from the leaves of Hibiscus rosa-sinensis (an agricultural waste) and red gypsum (waste from titanium dioxide manufacturing industry) are the two new drag reducers introduced. The extracted water soluble mucilage then converted to be oil soluble through adapted phase solubility inversion method. The objectives of this research is to analyze the effect of selected investigated materials based on solution concentration, fluid’s Reynolds number, pipe diameter and length of testing section. In order to achieve the objectives of this study, an experimental rig consists of three galvanized pipes of different diameters 0.0381m, 0.0254m and 0.0127m each 2m in length was built as closed loop liquid circulation system. The drag reduction ability of the water soluble mucilage was tested successfully with a maximum DR of 39% achieved in 0.0381m ID and 1.5m length pipe. The drag reduction ability of the oil soluble mucilage gives maximum DR of 47% achieved in 0.0381m ID and 1.5m length pipe. While gypsum powder reduces drag around 26% and 60% in water and diesel solutions respectively achieved in 0.0381m ID and 1.5m length pipe. The statistical drag reduction correlation was modeled with experimental data using STATISTICA software. As a conclusion, new environmentally friendly drag reducing agents were introduced to the field as an alternative to existing commercial additives and its effectiveness in improving the flow was proven experimentally.